Stakeholder engagement in social enterprise: designing a sustainable business model for the 'Food for Us' mobile application - Tantsi, Idah Thato (Rhodes University, Faculty of Commerce, Rhodes Business School)
This study aimed to develop a sustainable business model that is cognisant of the fundamental principles of social enterprises that can sustain the operation of the Food for Us mobile application that links farmers with buyers in Eastern and Western Cape, South Africa. The Food for Us mobile application lacks a supporting sustainable social business model to sustain its continued operations, hence the need to develop one. In the study, data was generated qualitatively underpinned by an interpretive paradigm, in three workshops guided by the Delphi method. A stakeholder salience model was applied to identify key stakeholders and their salience. Three key stakeholders, namely users (farmers and buyers), Experts (App developers) and the consortium were identified. The study concluded that developing a sustainable social, innovative business model requires substantive consultation with multiple stakeholders in society. Every stakeholder is important and possesses varying salience, hence stakeholder mapping is an important exercise. The study further concluded that financial sustainability and social inclusion are critical social enterprise elements to consider in the process. The undertaking to enhance financial sustainability opens an understanding on the importance of income streams, the key activities, and value propositions offered by the mobile application. The need to remain socially inclusive brings forth questioning of value propositions, accessibility, user friendliness towards stakeholder diversity and needs. The study offers a solution for the Food for Us mobile application in the form of a prototype which is ready for testing, and if desired results are achieved, this can enhance the much needed continued operations of the mobile application.
Keywords: Business planning -- South Africa; Sustainability -- South Africa; Mobile apps -- South Africa; Social responsibility of business -- South Africa; Social entrepreneurship -- South Africa; Food for Us (Application software)